2020
DOI: 10.1038/s41427-020-0232-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of perpendicular magnetic anisotropy and Dzyaloshinskii–Moriya interaction in thin ferromagnetic films by atomic-scale modulation of interfaces

Abstract: To stabilize nontrivial spin textures, e.g., skyrmions or chiral domain walls in ultrathin magnetic films, an additional degree of freedom, such as the interfacial Dzyaloshinskii-Moriya interaction (IDMI), must be induced by the strong spin-orbit coupling (SOC) of a stacked heavy metal layer. However, advanced approaches to simultaneously control the IDMI and perpendicular magnetic anisotropy (PMA) are needed for future spin-orbitronic device implementations. Here, we show the effect of atomic-scale surface mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 65 publications
1
21
0
1
Order By: Relevance
“…Микромагнитное моделирование проводилось в программном пакете MuMax3 [15], в котором решается уравнение Ландау−Лифшица−Гильберта [16] личина взаимодействия DMI изменялась в диапазоне 0−1.2 mJ/m 2 , что согласуется с экспериментальными данными [6,[17][18][19][20][21].…”
Section: исследуемые структуры и методика численного моделированияunclassified
“…Микромагнитное моделирование проводилось в программном пакете MuMax3 [15], в котором решается уравнение Ландау−Лифшица−Гильберта [16] личина взаимодействия DMI изменялась в диапазоне 0−1.2 mJ/m 2 , что согласуется с экспериментальными данными [6,[17][18][19][20][21].…”
Section: исследуемые структуры и методика численного моделированияunclassified
“…They found that the net iDMI increases as the difference between the interface quality of the top and bottom Co layer increases. In addition, Samardak et al 14 studied the effect of atomic-scale surface modulation on the iDMI in ultrathin films composed of 5d heavy metal/ferromagnet/4d (5d) heavy metal or oxide interface. They predicted that a significant enhancement of the iDMI by up to 2.5 times can be achieved through interface roughness engineering on the atomic scale.…”
Section: Introductionmentioning
confidence: 99%
“…13 The primary consideration in this field is related to ideal structural interfaces. Little attention has been paid to the disordered structure of thin films, 14,15 where the layers have surface roughness and undergo intermixing at the interfaces. Furthermore, theoretically and experimentally, it was demonstrated that the atomically intermixed ''ferromagnetic/heavy metal'' (FM/HM) interfaces could induce an extrinsic SOC, which enhances the spinorbit torque (SOT).…”
Section: Introductionmentioning
confidence: 99%